Association between occupational health and safety knowledge and behaviours among migrant workers: results from a cross-sectional study in China. Issue 12 (1st December 2020) - Hu, Ruwei; Hu, Nan; Liu, Ruqing; Shi, Leiyu; Shi, Jingrong; Ling, Li
Abstract : Objectives: To assess the relationship between occupational health and safety (OH&S)-related behaviours of migrating workers in China and their knowledge regarding OH&S laws and regulations (L&Rs). Materials and methods: We sampled 1282 migrant workers from 12 labour-intensive manufacturers in Guangdong, China, with a response rate of 98.6%. Self-reported questionnaires were completed by the participants. Logistic regression models were used to examine the association between OH&S-related behaviours and knowledge among migrant workers adjusting for their demographic features and the survey sites. Results: Migrant workers' behaviour of seeking occupational disease (OD) diagnosis and treatment was found to be statistically significantly correlated with their knowledge of all three OH&S L&Rs. A higher score of knowledge regarding these OH&S L&Rs is associated with a better chance to seek OD diagnosis and treatment. The ORs of the high-score group (subjects correctly answered more than one question) versus the low-score group (subjects correctly answered less than or equal to one question) are 2.02 (95% CI: 1.33 to 3.07) for Law of Occupational Disease Prevention and Treatment, 2.89 (95% CI: 1.65 to 5.09) for Regulations on Safe Management of Dangerous Chemicals and Regulations on Labor Protection for Using Toxic Substances in Workplace and 2.25 (95% CI: 1.34 to 3.77) for Work-Related Injury Insurance Regulations. However, knowledge about these L&Rs is not statistically significantly associated with OH&S-related protective behaviours such as wearing a mask or gloves at work. Conclusions: Knowledge of OH&S L&Rs helps migrant workers in China to seek OD diagnosis and treatment.